The last comics on Earth. 2, Too many villains! - Brallier, Max; Pruett, Joshua (Viking, 2024)
"Strange invaders from the Underverse are threatening the peaceful peoples of Apocalyptia, the Under Clowns from Clownlantis have come, and it's no laughing matter! Now Jack, June, Quint, and Dirk have to write and draw a sequel, while Lightning Boy, Moonstar, and Doc Baker help Savage Aloner face his primal fear of clowns and save Apocalyptia (again)! It's going to be even MORE wild than it sounds!" -- Page [4] cover.